Visual contents adaptation for colour vision deficiency using customised ICC profile. - Jang YG; Choi HI; Hong KS (Disability & Rehabilitation: Assistive Technology, 2010)
Purpose. Approximately, 1 of 12 persons in the world has colour vision deficiency (CVD), named colour blindness. While the amount of graphic information in digital contents is continuing to increase dramatically, assistive tools for colour vision deficiencies remain scarce. Methods. We developed a method to generate customised International Colour Consortium (ICC) colour profiles for patients suffering from CVD, which could adjust graphic contents according to individual needs. Compensation rules for the pale or dark range of red and green colours were established, and an ICC profile was generated using this set of rules. Results. The passing rate for Ishihara test was 99.5% when the generated profile was applied to 10 Ishihara plates and tested on individuals suffering from red deficiency, and green deficiency (5, and 15 participants, respectively). The time used to generate the compensation profile was 12.9 min on average, including the time taken to explain the test to the participants. Conclusion. Reliable results were achieved with a relatively low effort in comparison with methods currently utilised in professional clinics, and does not need expensive instruments.